The Impact of COVID-19 Pandemic on Psychiatric Emergency Department Visits – A Descriptive Study - Gonçalves-Pinho, Manuel (Psychiatr Q, 2020)
The coronavirus disease 2019 pandemic (COVID-19) has an important direct and indirect impact on both physical and mental health. We aim to describe the impact of an emergency state period due to COVID-19 on psychiatric emergency department (ED) visits. We conducted a retrospective observational study analysing all emergency visits occurring at a metropolitan psychiatric ED between March 19th and May 2nd 2019 and 2020 (the beginning/end date of the emergency state which Portugal was under due to COVID-19). Data regarding age, sex, diagnoses, admission date, discharge destiny and status were collected. Diagnoses were classified using the International Classification of Diseases version 9, Clinical Modification (ICD-9-CM). There was a 52·2% decrease on the number of psychiatric emergency visits during the emergency state period (n(2020) = 780 vs n(2019) = 1633 episodes). The decrease on psychiatric ED visits was greater in the female sex and in the younger age groups. Episodes with a primary diagnosis of Mood disorders lead the decrease on psychiatric ED visits with 68·3% less episodes. Schizophrenia and other psychotic disorders was the diagnosis group with the smaller decline (9·8% decrease). COVID-19 emergency state period had an important impact on the number and characteristics of psychiatric ED visits, reinforcing the great indirect effects of COVID-19 on mental health.